Performance of sulfur-doped graphitic carbon nitride loaded with silver for bisphenol a removal under solar irradiation - Lok, Li Wen (2017)
A facile method of fabricating Ag/S-doped g-C3N4 composite photocatalyst has been developed. The photocatalyst was characterized via XRD, UV-vis DRS, FT-IR, FESEM, EDS, and BET. Based on the results from characterization study, the Ag/S-doped g-C3N4 composite have well-distributed and highly crystalline Ag. The introduction of Ag nanoparticles on the surface of S-doped g-C3N4 has remarkably enhanced the photocatalytic efficiency for bisphenol A (BPA) removal as compared to S-doped g-C3N4. The Ag/g-C3N4 composite photocatalyst with 12 wt.% of Ag content showed the highest photocatalytic efficiency followed by 2 wt.%, 8 wt.%, 4 wt.% and S-doped g-C3N4. Through the photocatalytic degradation of BPA, it has found that the TOC removal was 48% while the Ag leaching was less than 40 μg L−1after 4 h of solar irradiation . Meanwhile, the effect of catalyst dosage and pH played crucial roles in the BPA removal. The results also indicated that the BPA removal efficiency increase with increasing pH. The possible reason could be due to the disassociated BPA ions (BPA- and BPA2-) can be degraded easier than BPA molecules while the superoxide radicals are more effectively at basic condition. Moreover, through the study on the mechanism of BPA degradation under visible light irradiation, with the addition of benzoquinone (BQ), the BPA removal efficiency decreased significantly from 95% to only 10%, indicating the active species of ⦁O2−played an important role whereas h+,⦁O2−, 1O2, and ⦁OH, played minor roles in the photocatalytic degradation of BPA. The reusability test on the photocatalyst showed relatively high stability for the removal of BPA under solar irradiation. It is concluded that 12 wt.% Ag/g-C3N4 composite would be a promising photocatalyst in the removal of BPA from water environment.